Magnetic state in URu2Si2, UPd2Al3, and UNi2Al3 probed by point contacts: Электpонные свойства металлов и сплавов - Naidyuk, Yu. G.; Kvitnitskaya, O. E.; Jansen, A. G. M.; Wyder, P.; Geibel, C.; Menovsky, A. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The antiferromagnetic (AFM) state has been investigated in the three heavy-fermion compoundsURu2Si2,UPd2Al3, and UNi2Al3 by measuring dV/dI(V) curves of point contacts at differenttemperatures 1.5-20 K and magnetic fields 0-28 T. The zero-bias maximum in dV/dI(V) for URu2Si2points to a partially gapped Fermi surface related to the itinerant nature of the AFM state, contrary to the case of UPd2Al3, where analogous features have not been found. The AFM state in UNi2Al3 has more similarities with URu2Si2. For URu2Si2, the same critical field of about 40 T along the easy axis c is found for all features in dV/dI(V), corresponding to the Néel temperature, the gap in the electronic density of states, and presumably the ordered moments.